Sensors: Harsh‐Environment‐Resistant OH‐Vibrations‐Sensitive Mid‐Infrared Water‐Ice Photonic Sensor (Adv. Mater. Technol. 8/2017). Issue 8 (17th August 2017) - Martínez, Javier; Ródenas, Airán; Stake, Andreas; Traveria, Miquel; Aguiló, Magdalena; Solis, Javier; Osellame, Roberto; Tanaka, Taro; Berton, Benoit; Kimura, Shigueo; Rehfeld, Nadine; Díaz, Francesc
Abstract : In article number1700085, Airán Ródenas and coworkers develop a mid‐infrared photonic sensor capable of detecting sub‐micron and micrometric water ice layers and identifying the type of water phase (liquid, solid, or metastable supercooled). Instead of working through evanescent‐field sensing, this sensor uses a tunneling mechanism dependent on the resonance frequencies of the water molecule OH‐vibrational modes. 3D sensor render performed by Alberto Trujillo.